Disruptive Technologies & Innovations: Managing the Change - Khurana, Vijay Kr.; Narula , S S (Gyan Management Journal, 2012)
" It is not the strongest of the species that survive, nor the most intelligent; but the most responsive to change."Modern era is an era of fast technological changes. Technological progress is continuously opening newer domains which were previously considered impossible. The rapid technological change is bringing forth positive as well as negative effects. Technology progress is changing the ways of doing business/work. Whenever any new disruptive technology/innovation emerges, it abruptly changes the business model and many a times it precipitates decline of existing firms dependent on older technologies. 131 year old Kodak became the latest giant to falter in the face of advancing technology which recently filed for bankruptcy protection under US Laws. Thus managing for change in the era of disruptive technologies & innovations has become uphill task for modern organizations.This paper highlights the difficulties faced by the Organizations which are having sole reliance on competitiveness through sustaining innovations. The paper explores the impact of disruptive technologies & innovations on business environment & organizations. The paper provides insight into some of the new emerging technologies & innovations which will change our way of doing work in coming future. The paper also explores the ways to respond to and cope up with the change introduced by Disruptive Technologies & Innovations.
Keywords: Disruptive technology; Sustaining innovation; Value network; Competition